The Life and Death of a Child: Mortuary and Bodily Manifestations of Coast–Interior Interactions during the Late Formative Period (AD 100–400), Northern Chile. Issue 1 (March 2022) - Torres-Rouff, Christina; Pimentel, Gonzalo; Pestle, William J.; Ugarte, Mariana; Knudson, Kelly J.
Abstract : Camelid pastoralism, agriculture, sedentism, surplus production, increasing cultural complexity, and interregional interaction during northern Chile's Late Formative period (AD 100–400) are seen in the flow of goods and people over expanses of desert. Consolidating evidence of material culture from these interactions with a bioarchaeological dimension allows us to provide details about individual lives and patterns in the Late Formative more generally. Here, we integrate a variety of skeletal, chemical, and archaeological data to explore the life and death of a small child (Calate-3N.7). By taking a multiscalar approach, we present a narrative that considers not only the varied materiality that accompanies this child but also what the child's life experience was and how this reflects and shapes our understanding of the Late Formative period in northern Chile. This evidence hints at the profound mobility of their youth. The complex mortuary context reflects numerous interactions and long-distance relationships. Ultimately, the evidence speaks to deep social relations between two coastal groups, the Atacameños and Tarapaqueños. Considering this suite of data, we can see a child whose life was spent moving through desert routes and perhaps also glimpse the construction of intercultural identity in the Formative period.